PHOSPHATIC COLUMNAR STROMATOLITES FROM THE UPPER JURASSIC OF THE ORENBURG AREA OF THE PERIURAL REGION - Silant'yev V.N. (My University, 1989)
Jurassic columnar stromatolites are considered to be a rarity in the world; in the USSR they have heretofore never been described. Columnar stromatolites have been found for the first time in the USSR in Late Jurassic (Oxfordian-Kimmeridgian) deposits, and it turns out that their mineral basis is not carbonates (as in most known stromatolite structures), but phosphates. This, on the one hand, testifies to a far more extensive occurrence of Jurassic stromatolites than was previously though and, on the other hand, to the possibility that stromatolite-forming bacterial-algal assemblages of organisms formed not only microgranular, but also concretionary phosphorite ores. The columns are predominantly spindle-shaped, pear-shaped or subcylindrical, with no discernible branching, sometimes with swellings and constrictions, and with a rough knobby, more rarely smooth level surface; they are clearly separated from each other and from the surrounding glauconite-quartz sand. Transverse sections through the columns are round or oval.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская